Corrigendum: Assessment of risk scores to predict mortality of COVID-19 patients admitted to the intensive care unit (Front. Med., (2023), 10, 1130218, 10.3389/fmed.2023.1130218) - Nogueira, Matheus Carvalho Alves (2024)
In the published article, there was an error in Table 2 as published. The p-value for the comparison between ABC2-SPH and SAPS-3 (in line 7 of the table) was displayed as 0.0046, but the correct p-value is 0.0446. The corrected Table 2 and its caption “Comparison between ABC2-SPH and other scores.” appear below. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. Comparison between ABC2-SPH and other scores. AUROC, area under the ROC curve. ue to the multiple comparisons, alpha was corrected using the Bonferroni method. ABC2-SPH has higher discrimination ability. The bold values indicate which p-values are lower than the alpha, meaning that the AUROC of ABC2-SPH is larger than that of the score being compared.